2008
DOI: 10.2319/062707-296.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the Dental Arch Form Using a Preadjusted Appliance with Premolar Extraction in Class I Crowding

Abstract: It is necessary to anticipate that the upper dental arch form will become tapered during extraction treatment for Class I crowding and to select an appropriate arch form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Miyake, Ryu and Himuro 25 compared the dental arch form at baseline and after the extraction of premolars in individuals with Class I crowding treated with preadjusted brackets. They found that the maxillary dental arch might become tapered after treatment with extractions.…”
Section: Discussionmentioning
confidence: 99%
“…Miyake, Ryu and Himuro 25 compared the dental arch form at baseline and after the extraction of premolars in individuals with Class I crowding treated with preadjusted brackets. They found that the maxillary dental arch might become tapered after treatment with extractions.…”
Section: Discussionmentioning
confidence: 99%
“…Several points were used for the representation of the posterior teeth, thus providing more information about their spatial position and inclination. Other studies have used reference points on the calculated centroids of the occlusal surfaces (35), at contact points (14), at the facial axis point (18,36), or on glass beads simulating bonded brackets (7).…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have focused on the normal or ideal dental arch and have used algebraic or geometric formulae to describe it. Such geometric figures and mathematical functions, most of which enforce symmetry, include: semicircle (10), ellipse (1,11), parabola (12), hyperbola (13), catenary curve (14), the cubic spline function (15), conic sections (8,16), polynomial European Journal of Orthodontics, 2016, 202-211 doi:10.1093/ejo/cjv019 Advance Access publication 3 April 2015 functions, including the fourth-order polynomial (17,18) and the sixth-order polynomial (7,9), Euclidean distance matrices (19), Fourier series (20), and the beta function (3,9). Mixed models have also been used, such as, ellipse and parabola (21), a semicircle joined to straight segments (10) and a combination of the polynomial, parabola and hyperbolic cosine functions (22).…”
Section: Introductionmentioning
confidence: 99%
“…The size of pentamorphic pattern is the research result of size average and dental arch shape conducted by Ricketts to Caucasoid race, thus if the 12 which indicate that race difference causes the difference in dental arch shape.…”
Section: Discussionmentioning
confidence: 99%